COVID-19 and Online Learning: A Community College Perspective (Comparative & International Education Series, 2022)
This chapter attempts to examine the experience of faculty and students during the pandemic and, taking an equity-minded approach, offers a set of recommendations to identify opportunities that the online transition experience has brought to community colleges.How to cite in APA:Siddiqi, M. (2022). COVID-19 and online learning: A community college perspective. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 53-68). STAR Scholars.